A new species of Galendromimus Muma from Brazil (Acari: Phytoseiidae), with a review of the tribe Galendromimini Chant & McMurtry - Demite, Peterson R.; Gondim, Manoel Jr. G.c.; Lofego, Antonio C.; de Moraes, Gilberto J. (Zootaxa, 2014)
The genus Galendromimus Muma and the tribe Galendromimini Chant & McMurtry are redefined to accommodate a new species, Galendromimus (Galendromimus) roraimensis sp. n., described in this paper based on specimens collected in the state of Roraima, northern Brazil. The new species differs from other Galendromimus mainly by having dorsal shield seta z3 present. A dichotomous key to separate the species of Galendromimini is presented.